2010
DOI: 10.1103/physreva.82.053826
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a continuous-variable quadripartite cluster state from a single optical parametric oscillator

Abstract: We examine the feasibility of generating continuous-variable multipartite entanglement in an intracavity concurrent downconversion scheme that has been proposed for the generation of cluster states by Menicucci et al. [Phys. Rev. Lett. 101, 130501 (2008)]. By calculating optimized versions of the van Loock-Furusawa correlations we demonstrate genuine quadripartite entanglement and investigate the degree of entanglement present. Above the oscillation threshold the basic cluster state geometry under considerati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
(100 reference statements)
1
9
0
Order By: Relevance
“…The search for optimal entanglement witnesses for this system is a promising approach to illuminate this question. Note that previous work has shown that multipartite cluster-state generation, which was experimentally demonstrated in a single OPO below threshold [12], should actually fail above threshold [13]. However, the multipartite entanglement that we discovered in the simple OPO above threshold would certainly be useful for quantum communication applications, such as quantum secret sharing.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The search for optimal entanglement witnesses for this system is a promising approach to illuminate this question. Note that previous work has shown that multipartite cluster-state generation, which was experimentally demonstrated in a single OPO below threshold [12], should actually fail above threshold [13]. However, the multipartite entanglement that we discovered in the simple OPO above threshold would certainly be useful for quantum communication applications, such as quantum secret sharing.…”
Section: Discussionmentioning
confidence: 57%
“…In Section 3, we solve the equations of motion for the system by employing a linearization procedure. We are certainly aware that more sophisticated treatments exist [13,[16][17][18][19] and may indeed be interesting to use in order to explore this system further. In particular, it is worth mentioning the new physics of noncritical squeezing generation-that is, squeezing independent of the system parameters such as pump amplitudein the transverse spatial modes of an OPO, which was recently predicted via the phenomena of spontaneous symmetry breaking [20,21] and pump clamping [22], the latter having already been observed in the laboratory [23].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Ref. [7], the system has an oscillation threshold and for the parameters used here the critical pump amplitude is c = 61.8. The parameters used in the following calculations are γ = 1, χ = 0.01 and = 0.94 c , giving a pump rate approximately 12% below threshold in intensity.…”
Section: Resultsmentioning
confidence: 99%
“…The system considered here is a pumped optical cavity containing a χ (2) non-linear crystal, as investigated theoretically in Ref. [7]. We extend our analysis to incorporate the results of a full spectral analysis in the frequency domain.…”
Section: System and Methodsmentioning
confidence: 99%
See 1 more Smart Citation